Dispersion relations and QCD [Quantum ChromoDynamics] factorization in hard reactions - Anikin, I. V. (Array, 2008)
Summary: We study analytical properties of the hard exclusive process amplitudes. We found that QCD factorization for deeply virtual Compton scattering and hard exclusive vector meson production results in the subtracted dispersion relation with the subtraction constant determined by the Polyakov-Weiss D-term